All Days 2008
DOI: 10.2523/iptc-12668-ms
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Evaluation of an Innovative Acid System for Fracture Stimulation of Carbonate Reservoirs in Saudi Arabia.

Abstract: TX 75083-3836, U.S.A., fax +1-972-952-9435. AbstractAcid Fracturing has been a successful method to stimulate the Khuff Carbonate wells of Saudi Arabia since the beginning of the gas development program. Various types of acid systems including conventional, emulsified and surfactant-based have been used in an attempt to achieve optimum fracture length and conductivity. Acids used for these treatments have been typically formulated with 28-wt% HCl and have been used successfully to increase production from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Al-Ghurairi et al (2006) and Duverney et al (2007). A few workers suggested that fracture damage was the cause for the unusual behaviour such as Elbel and Ayoub (1992) and Garzon et al (2008). In this study, causes of fractured wells exhibiting unusual flow behaviour is investigated in detail, below is a brief review of all publications on the problem.…”
Section: Research Problem Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Al-Ghurairi et al (2006) and Duverney et al (2007). A few workers suggested that fracture damage was the cause for the unusual behaviour such as Elbel and Ayoub (1992) and Garzon et al (2008). In this study, causes of fractured wells exhibiting unusual flow behaviour is investigated in detail, below is a brief review of all publications on the problem.…”
Section: Research Problem Reviewmentioning
confidence: 98%
“…However, the authors did not explain what caused the behaviour and why they were unable to match typical linear or bilinear fracture flow behaviour on log-log pressure versus elapsed time diagnostic plot. Garzon et al (2008) investigated fracture flow behaviour and stated that the cause of the problem is related to improperly performed frac jobs. Their interpretation of the behaviour was attributed to damage within the fracture near the wellbore that prevents fracture flow into the wellbore.…”
Section: Research Problem Reviewmentioning
confidence: 99%